IOMT Security and Anomaly Detection in Medical Images ‎Using AI - Mishra, Dr. Nidhi; Nayak, Ashu (International Journal of Basic and Applied Sciences, 2025)
The extensive use of information and communication technology (ICT) has transformed every aspect of life as the world moves closer to ‎digitalization. There is no denying that ICT has changed how people communicate, live, work, and study. The Internet of Things, or things, ‎is a powerful combination of critical ICT technologies, with integrated hardware, software, and other technologies for connecting and ‎sharing data with other systems and devices over the Internet. An Internet of Things (IoT) device is any electronic device that can be used in ‎a wide range of social contexts, including connected industries, transportation, healthcare, smart supply chains, smart farms, smart cities, ‎smart grids, and many more. This includes wearable technology and hardware. The Internet of Medical Things (IoMT) is a real-world ‎application of the Internet of Things (IoT) in the healthcare sector, enabling patients to receive better healthcare and enjoy a higher quality of ‎life. It provides seniors and patients with real-time healthcare services, support, and caregiving using Internet-enabled smart devices. The ‎current coronavirus disease (COVID-19) has increased the demand for remote patient care due to a paucity of resources and healthcare ‎facilities, in contrast to the enormous global demand for these services and facilities. Therefore, COVID-19 has played a significant role in ‎the shift of the present healthcare system towards remote care. Even with advancements in the healthcare sector and the apparent benefits of ‎integrating it with IoT, moving all forms of communication online is a logical next step. It opens the door for potential security lapses in the ‎ongoing IoMT communication, providing adversaries with unauthorized access to vital health data that could be misused for malicious ‎intent‎.